Estudantes com deficiência intelectual na educação de jovens e adultos: interfaces do processo de escolarização - Freitas, Mariele Angélica de Souza (Universidade Federal de São Carlos, 2014)
Subject rarely discussed in the context of special education, including students with intellectual disabilities in the halls of the regular school system, in the form of Youth and Adult Education (EJA) reinforces the principles of construction of an inclusive society in which, expressed equal rights and social and educational opportunities. The present study had as main objective to understand the educational process of young people with intellectual disabilities who attend adult education. The specific objectives were: a) know the process of education to the students with intellectual disabilities in EJA, b) identify the conditions of work of teachers EJA along to students with intellectual disabilities and c) identify the meaning assigned to students by EJA intellectual disabilities and their caregivers. The study is characterized as a qualitative research with characteristics of case study. The research was conducted in a room EJA village school situated in the State of São Paulo, in this study two girls with intellectual disabilities in the form of AYE character of fundamental and regular education (nighttime), their mothers and the teacher responsible for the EJA room. The survey of empirical data were collected through desk research, semi-structured interviews with all participants, free observation and through a field diary. In order to cover all aspects of the phenomenon studied, the survey was analyzed through observations, notes from the field diary and was subsequently analyzed by themes. The results showed that the participants had, throughout his school career, long periods of change and long stays in one step, finally reaching the EJA. Regarding the meaning ascribed to EJA, find data that underscored the character of this modality enhancement understood as the only space that families have to meet young people and adults with intellectual disabilities. Regarding the results of the interview with the teacher, the reports reveal the countless difficulties that pervade the precarious condition of the teacher s work in our country. Regarding the data found on the expectations of future life, we realize that the process of perception, experiences and the experiences of mothers compared to daughters with intellectual disabilities can significantly influence their attitudes and how visualize the process of education of young people, process this can be permeated by fear and uncertainty. Regarding the completion of enrollment in Youth and Adult Education, observed that both mothers do not have clarity on what is the social function of EJA since reported that daughters can remain in this mode indefinitely, possibly mothers have this conception of the EJA due to shortage of public policies that address this population of intellectually disabled in young adulthood. We conclude that the inclusion of students with intellectual disabilities in the halls of the regular school system, in the form of Youth and Adult Education is still a little discussed topic that deserves greater attention from the academic community due to the importance of this type.
Keywords: Educação de jovens e adultos; Escolarização; Deficiência intelectual; Special education; Youth and adults; Schooling; Intellectual disabilities; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL